2021
DOI: 10.2147/copd.s324952
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose-Derived Mesenchymal Stem Cells Ameliorate Elastase-Induced Emphysema in Mice by Mesenchymal–Epithelial Transition

Abstract: Purpose: Chronic obstructive pulmonary disease (COPD) is a worldwide problem because of its high prevalence and mortality. However, there is no fundamental treatment to ameliorate their pathological change in COPD lung. Recently, adipose-derived mesenchymal stem cells (ADSCs) have attracted attention in the field of regenerative medicine to repair damaged organs. Moreover, their utility in treating respiratory diseases has been reported in some animal models. However, the detailed mechanism by which ADSCs impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…We then tested COPD and non-COPD AD-MSC therapeutic potential in vivo by administrating intratracheally two doses of cell suspensions and found that both cohorts were capable of reducing emphysema in our elastase mouse model, as demonstrated by reduction in more than 50% of the emphysematous areas. Other preclinical studies from Antunes et al [ 25 ] and Fujioka et al [ 26 ] support the therapeutic applicability of AD-MSC in reducing elastase-induced emphysema; however, they only tested AD-MSC from healthy human subjects. Two phase I/II clinical studies have started to evaluate the effect of autologous AD-MSC as single cells or in the form of stem vascular fraction (SVF) applied right after isolation intravenously in patients with COPD (NCT04433104 and NCT02216630 respectively).…”
Section: Discussionmentioning
confidence: 99%
“…We then tested COPD and non-COPD AD-MSC therapeutic potential in vivo by administrating intratracheally two doses of cell suspensions and found that both cohorts were capable of reducing emphysema in our elastase mouse model, as demonstrated by reduction in more than 50% of the emphysematous areas. Other preclinical studies from Antunes et al [ 25 ] and Fujioka et al [ 26 ] support the therapeutic applicability of AD-MSC in reducing elastase-induced emphysema; however, they only tested AD-MSC from healthy human subjects. Two phase I/II clinical studies have started to evaluate the effect of autologous AD-MSC as single cells or in the form of stem vascular fraction (SVF) applied right after isolation intravenously in patients with COPD (NCT04433104 and NCT02216630 respectively).…”
Section: Discussionmentioning
confidence: 99%
“…As the primary risk factor for COPD, CS is largely employed in basic research. Other experimental stimulants include porcine pancreatic elastase (PPE), the main alternative for CS [ 167 ], papain [ 168 ], air pollution [ 169 , 170 ], or biomass burn [ 171 ], either alone or combined with other provocations such as lipopolysaccharide (LPS) [ 172 ]. Some protocols consider mixing CS and other stimuli to provoke an exacerbation superimposed on tissue destruction, typical of emphysema [ 173 ].…”
Section: Oxidative Stress and Inflammation In Copd And Emphysemamentioning
confidence: 99%
“…The Mesenchymal-Epithelial Transition and Metaplasia progenitors as opposed to terminally differentiated cell types 9,21,22 . MET does not usually replace one differentiated cell type with another differentiated cell type 1,9,21,22 , making it difficult to explicitly define the process as a form of metaplasia.…”
Section: Perspectivesmentioning
confidence: 99%
“…MET does not usually replace one differentiated cell type with another differentiated cell type 1,9,21,22 , making it difficult to explicitly define the process as a form of metaplasia. Rather, MET often involves the reprogramming of undifferentiated cells such as mesenchymal stem cells (MSCs) 21 , embryonic stem cells (ESCs) 1 , and cancer stem cells (CSCs) 2,22 .…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation